2015
DOI: 10.15388/informatica.2015.60
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless Estimation of Wind Speed by Soft Computing Methodologies: A Comparative Study

Abstract: This paper shows a few novel calculations for wind speed estimation, which is focused around soft computing. The inputs of to the estimators are picked as the wind turbine power coefficient, rotational rate and blade pitch angle. Polynomial and radial basis function (RBF) are applied as the kernel function of Support Vector Regression (SVR) technique to estimate the wind speed in this study. Instead of minimizing the observed training error, SVR_poly and SVR_rbf attempt to minimize the generalization error bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…53,54 RBF kernel does not need complicated quadratic programming problem but required only several linear equations for a solution. 55 Hence, RBF is adopted in this study, with the parameter. Equation (16) shows the nonlinear radial basis kernel function:…”
Section: Svmmentioning
confidence: 99%
“…53,54 RBF kernel does not need complicated quadratic programming problem but required only several linear equations for a solution. 55 Hence, RBF is adopted in this study, with the parameter. Equation (16) shows the nonlinear radial basis kernel function:…”
Section: Svmmentioning
confidence: 99%
“…Also, it should be noted that as the wind speed is not accurately measurable, so, ) in (23) is an unknown variable. Substituting (23) into (21) leads to,…”
Section: Desired Operational Mode and Control Objectivesmentioning
confidence: 99%
“…In [22] a nonstandard extended Kalman filter is developed to estimate the wind speed for maximum power extraction of variable speed wind turbines. In [23] a comparative study of using soft computing methodologies for estimation of wind speed was presented. A review of the effective wind speed estimation-based control of wind turbines can be found in [24].…”
Section: Introductionmentioning
confidence: 99%
“…ANN has been applied to model renewable energy systems, economics, psychology, subsurface two-phase flow and many more (Abidoye and Bello, 2017; Abidoye and Das, 2015; Kalogirou, 1999). Authors like Petković et al (2015) have suggested soft computing for wind farm analysis. Soft and simplified computational techniques will overcome the cost and complexity associated with flow-physics-based computational fluid dynamic (CFD) simulators that are employed in works like that of Das et al (2014) and Abidoye and Wairagu (2013).…”
Section: Introductionmentioning
confidence: 99%